Examining the Role of Islamic Financing in Enhancing Bank Efficiency and Stability: A Moderation Analysis of NPF - Muhammad Rafi Zaidan Ariq; Igo Febrianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Using Non Performing Financing (NPF) as a moderating variable, this study looks at how profit sharing and profit margin financing affect the effectiveness and stability of Islamic banks in Indonesia. The primary topic discussed is how various Islamic financing arrangements affect the operational effectiveness and financial stability of banks, as well as whether credit risk enhances or diminishes these connections. This study aims to examine the direct impacts of financing modalities as well as the moderating influence of NPF on the performance of Islamic banks. Based on secondary data from eight Islamic banks in Indonesia between 2018-2024, this study employs a quantitative methodology using panel data regression and Moderated Regression Analysis (MRA). The findings indicate that while profit margin financing has no discernible impact on efficiency, profit sharing financing has a favorable and considerable impact. Profit margin financing has a negative and negligible impact on stability, whereas profit sharing financing has a positive but negligible impact. Additionally, by changing the direction of influence, NPF significantly moderates the association between profit sharing financing and both efficiency and stability. However, it does not significantly moderate the effect of profit margin financing on efficiency, but it does on stability. In summary, the effectiveness of Islamic financing is heavily reliant on risk management, especially credit risk control, where NPF is a key factor in evaluating whether financing can improve stability and efficiency in Islamic banks.